Facile Synthesis of Super-hydrophobic CuO Film on Copper Substrate - Nie, Rongchun; Xu, Chuyang; Wang, Yanfen; Li, Benxia (Asian Journal of Chemistry, 2013)
Super-hydrophobic metal films have attracted significant attention due to their many advantage and wide applications. In the present work, we report a convenient one-step route for a large scale of butterfly-like or flower-like CuO microstructures constructed from nanoplates on copper substrate at low tempreture. After octadecane thiol hydrophobization, the film exhibited excellent super-hydrophobicity and little sliding angle, which could be attributed to combination of the improved dual scale roughness of CuO and the octadecane thiol coating with low surface energy. The super-hydrophobic metal coating may be applicable for multiple fields such as self-cleanning or anticorrosion field.